WordGirl : Coalition of Malice - Karwowski, Chris (Kaboom!, 2011)
When WordGirl's arch-villains the Butcher, Mr. Big, Dr. Two-Brains, Granny May, and Chuck, the Evil Sandwich-Making Guy, form the Coalition of Evil, WordGirl and Captain Huggy face have a problem on their hands. Then, WordGirl must come to the rescue when her biggest fans fall victim to the wicked Lady Redundant Woman.